Senam Irama Lagu Gizi Seimbang Meningkatkan Kebugaran Pada Anak Sekolah - Een Juliasti; Mury Kuswari; Idrus Jus’at (Journal Sport Area, 2020)
Physical activity on students in Jakarta is the lowest if it is compared to various regions in Indonesia. The low physical activity has an impact on the declining of health and fitness so that it affects toward the risk of various non-communicable diseases. The purpose of this research is to know the influence of gymnastics rhythm of Gizi Seimbang’s song to the level of fitness on students in State Elementary School Kebon Jeruk 08 Pagi West Jakarta. The type of research uses design experimental quasi research with design of Pre test - post test group control design. This design involves two groups of subjects, one is given an experimental group and one group is not enforced (control group). The population of this study are children aged 10-12 years old with 60 respondents (30 students of gymnastic group and 30 control group students) with gymnastics 3x/week for 12 times. Data analysis use t-dependent test, wilcoxon test because the data is not normally distributed. The result of the research shows that there is the influence of rhythmic gymnastics of Gizi Seimbang’s song to the significant fitness level (p value = 0.0001). Based on the results of this study, gymnastics rhythm of Gizi Seimbang’s song increases the level of fitness compared with control group on students in State Elementary School Kebon Jeruk 08 Pagi West Jakarta.